Supreme Court Circular Legislation Ratio Number 4 Of 2016 Related to Reserved Good Faith Buyer - Ihsan, Ahmad Yulianto; Hariri, Achmad; Stansyah, Dedy (Universitas Muhammadiyah Tangerang, 2024)
The land sale and purchase dispute in this case drags the seller who has sold the same object to two buyers in two transactions. The second buyer (plaintiff) filed a lawsuit against the first buyer (Defendant II). The legal position is a dilemma. Both buyers feel they have rights to the disputed land because they have purchased the same object from the seller. To prove who the right buyer is, the judge needs to consider the principle of